The Effects of Tomato Intercropping with Medicinal Aromatic Plants Combined with Trichoderma Applications in Organic Cultivation - Magdalena Szczech; Beata Kowalska; Frederik R. Wurm; Magdalena Ptaszek; Anna Jarecka-Boncela; Paweł Trzciński; Kaja Borup Løvschall; Sara T. Roldan Velasquez; Robert Maciorowski (Agronomy)
To increase biodiversity in tomato cultivation, two herbal aromatic plants, thyme (Thymus vulgaris) and basil (Ocimum basilicum L.), were introduced as companion plants. Their role was to improve crop plant growth and stress resistance. Moreover, the effect of the soil application of Trichoderma microbial preparations on tomato growth parameters and yield, in combination with companion plants, was studied. Ligno-cellulose multi-layer microcapsules with Trichoderma atroviride TRS14 spores (MIC14) and the commercial preparation Trianum G (TG) were used as microbial preparations. This experiment was carried out in a certified organic field. Tomato plants were intercropped with thyme or basil in the arrangement of two tomato rows alternating with one herbal row. In all intercropping arrangements and in the control (tomato plants grown without herbs), subplots were sectioned. The soil in the subplots was amended with the MIC14 and TG preparations used at a concentration of 104 spores g−1 of the soil and planted with tomato transplants. No control measures were applied during tomato growing, and the plants were naturally infected with late blight. Tomato plant growth parameters and yield were assessed, and late blight severity was monitored. The degree of soil colonization by Trichoderma fungi and the effect of these applications on soil microbial activity and biodiversity (dehydrogenases activity, EcoPlates AWCD, and Shannon index) were evaluated. The results clearly showed a significant influence of thyme and basil on tomato growth and yield in organic production. The cultivation of thyme adjacent to tomatoes had a beneficial effect on the development of the root system and the number of flowers and fruits on the crop plants. Basil, on the other hand, clearly decreased tomato yield and adversely affected the effect of Trichoderma applications by reducing root system development. Moreover, basil as a companion plant increased late blight symptoms. Both Trichoderma strains colonized soil, but they had no significant effect on the microbial activity or metabolic potential measured on the EcoPlates with the use of the BIOLOG system. However, a decrease in dehydrogenases activity was noted. In organic cultivation, the Trichoderma preparations used had no significant effect on tomato yield, opposite to its increase in integrated tomato production.